ENGINEERING DESIGN OF BREAKWATER STRUCTURES FOR COASTAL EROSION MITIGATION: A CASE STUDY IN SRAGI, SOUTH LAMPUNG - Suciana Suciana; Mustarakh Gelfi; Pandu Nababan (Jurnal Ilmiah Teknik Sipil, 2025)
Kuala Jaya Beach, located in Bandar Agung Village, Sragi District, South Lampung, is experiencing severe coastal erosion, leading to shoreline retreat and degradation of coastal ecosystems. This study presents the engineering design of breakwater structures as a mitigation strategy. The design process considered key parameters, including significant wave height and period, Highest High Water Level (HHWL), wave refraction and breaking coefficients, wave set-up, projected sea level rise, wave run-up, and structural stability based on Terzaghi and Hudson equations. Wave characteristics were analyzed using a Weibull distribution for a 50-year return period, yielding a significant wave height of 2.26 m and a period of 6.98 s. Tidal analysis used the Admiralty method to determine an HHWL of 0.63 m. Three types of armor layers were evaluated: natural rock, concrete cubes, and geobags. The resulting crest widths were 2.0 m, 1.8 m, and 2.8 m, with corresponding elevations of 3.76 m, 3.0 m, and 3.6 m. Two breakwaters, 1000 m and 800 m in length, were positioned at a depth of 5 m near the wave-breaking zone. Stability analysis showed armor to secondary layer ratios of 2.4 for concrete cubes and 2.0 for natural rock. All designs allow controlled seepage, dissipating wave energy, and effectively preventing further shoreline retreat.